(untitled) (Intent Research Scientific Journal, 2025)
The article is devoted to methodological approaches to teaching sections and cross-sections, as well as an analysis of their role in the development of spatial thinking. Various teaching methods are considered, including visualization, modeling and the use of software, as well as the influence of pedagogical technologies such as virtual and augmented reality on the understanding and perception of three-dimensional objects. Particular attention is paid to the integration of theory and practice, as well as the importance of examples and practical tasks in the learning process. The article also offers scientific and methodological recommendations for improving teaching, and discusses prospects for further research and development of the topic in the field of education.